GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

The MetaBó-Bainne Study – characterisation of the milk metabolome from a seasonal pasture-based dairy system using 1H-NMR spectroscopy - Paula Rojas-Gómez; Raghunath Pariyani; Michael Dineen; Denis Lynch; Lorraine Bateman; Eoghan Roche; Anita R. Maguire; Noel A. McCarthy; Thomas Brendan Murphy; James A. O’Mahony; Tom F. O’Callaghan (Food Chemistry, 2026)

Non‐native pink salmon Oncorhynchus gorbuscha carcasses benefit native benthic macroinvertebrates - Hui Wei; Gordon H. Copp; Rasmus B. Lauridsen; Tea Bašić; Phil I. Davison; John F. Murphy; James L. Pretty; Michał E. Skóra; Gabriela Zemelka; John Iwan Jones (Journal of Fish Biology, 2026)
The invasion of the North Atlantic by pink salmon Oncorhynchus gorbuscha has raised concerns regarding their impact on coastal rivers. Although the influence of marine‐derived nutrients from returning adult O. gorbuscha on rivers in their native range has received much attention, the ecological consequences of invasive O. gorbuscha for ecosystems outside the native range are largely unknown. To investigate the impact on the density and community structure of benthic macroinvertebrates, O. gorbuscha carcasses were added to 12 experimental channels for 60 days at three treatment levels (control, no carcass; low and high, loading rates). Stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) were used to determine if nutrients from carcasses were incorporated into native biota. The density of macroinvertebrates increased close to the carcasses in the high‐addition treatment, suggesting aggregation. Furthermore, macroinvertebrates had a higher δ 15 N near to the carcasses in the low‐ and high‐addition treatments after 30 days, indicating uptake from the carcasses. The higher δ 15 N of willow moss Fontinalis antipyretica in carcass‐addition treatments indicated that primary producers could also assimilate nutrients from the decomposition of carcasses. Whilst the addition of carcasses resulted in the increased density of small individuals of macroinvertebrates, this did not propagate to changes in community composition in this relatively short experiment. Overall, the results suggest that native biota might benefit from the marine‐derived nutrients transported to streams by invasive O. gorbuscha , however, the long‐term effects of such nutrient/energy subsidies on receiving ecosystems require further investigation.

Temporal Biomarker Profiles Following Non-Surgical Spinal Cord Concussion - Taylor M. Dickson; Anastasiya Loos; Malaika Amin; Juliana Vivas Lopez; Susan F. Murphy; Pamela J. VandeVord; Kelly C. S. Roballo (Journal of Molecular Neuroscience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Increasing Efficiency of Detection and Validation of Baleen Whale Call Presence on Large Acoustic Datasets: A Case Study Using Sei Whale Downsweeps Recorded in Atlantic Canada - Gabrielle F. Macklin; Hilary B. Moors‐Murphy; Marty L. Leonard (Marine Mammal Science, 2026)
As passive acoustic monitoring (PAM) datasets expand, studies increasingly use automated detectors to analyze baleen whale presence. However, detector errors like false positives (impacting precision, P; proportion of detected calls that are correct), and false negatives (impacting recall, R; proportion of available calls successfully detected) necessitate manual validation. Here, we demonstrate a tiered detection and validation approach to improve efficiency in sei whale ( Balaenoptera borealis ) call presence analysis that aims to maximize R while removing false positives. Using two detectors on eastern Canadian datasets, we tested multiple parameter settings, selecting one tier that captured only high‐quality calls (High‐P), one tier that captured most calls present but included more false positives (High‐R), and one tier that balanced the P and R values (Mid). To assess daily call presence, validation proceeded sequentially across tiers from High‐P to Mid to High‐R. For each subsequent tier, detections were only reviewed from days in which sei whale calls had not yet been confirmed. For both detectors, using this tiered approach reduced the overall manual validation effort (number of detections reviewed) when compared to validating the highest recall original outputs alone. This efficient strategy maintains accuracy in PAM studies and could be used for other species.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Diameter, height, and volume as macroscopic predictors of photocarcinogenesis in UV-induced SKH1 papules - Mehdi Boostani; Alaina F. Carman; Erin C. Tracy; Sean P. Murphy; Rhea Carmel Glen Rodrigues; Katalin Ferenczi; Gillian Weston; Olayemi Sokumbi; Gyorgy Paragh; Wendy J. Huss (Journal of Photochemistry and Photobiology B: Biology, 2026)

Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

Pork safety across Vietnam's traditional markets: Microbial contamination and vendor knowledge, attitudes, and practices - Trang Thi Huyen Le; Vivian Hoffmann; Kate Ambler; Mike Murphy; Sinh Dang-Xuan; Johanna F. Lindahl; Elisabeth Rajala; Steven Lâm; Sofia Boqvist; Fred Unger; Hung Nguyen-Viet (Preventive Veterinary Medicine, 2026)

Circadian rhythm of amyloid-β in the olfactory bulb and cerebellum of wild-type and APPxPS1 knock-in mice indicates a loss of rhythmicity in regions more vulnerable to amyloid pathology - Valeria A. Buzinova; Carrie E. Johnson; Savannah M. Turton; Sarah E. Barth; Samantha Padgett; M. Tyler Maisel; Katharina Kohler; Haleigh R. Whitlock; Adam D. Bachstetter; Sridhar Sunderam; Bruce F. O’Hara; Marilyn J. Duncan; et al. (Biogerontology, 2026)

Correction: Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2026)

Integrating a pilot scale Spirulina biorefinery into a local bioeconomy: A comparative life cycle assessment of environmental mitigation strategies - L. Braud; K. McDonnell; F. Murphy (Algal Research, 2025)

P18-82 validation of scinora media for the culture of airway relevant cell lines: progress towards an animal-free airway model for nanomaterial toxicity testing - K. Mcallister; F. Murphy; B. Thalmann (Toxicology Letters, 2025)

Responses of small mammals to prescribed low-intensity fire: Genetic insights from a northern Australian fire experiment - Alexander R. Carey; Georgina Neave; Teigan Cremona; Hugh F. Davies; Brett P. Murphy; Geoffrey J. Cary; Tiwi Rangers; Toby Barton; Sam C. Banks (Biological Conservation, 2025)

Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2025)
The climate of the Maritime Continent, including Singapore, is influenced by a wide range of tropical drivers including the El-Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Madden–Julian Oscillation (MJO), and equatorial wave activity. In Singapore, the rainfall pattern is often marked by episodes of short intense rainfall bursts, primarily driven by mesoscale convective systems, such as Sumatra squall lines. These episodes often result in local flash floods and strong wind bursts. Here we analyse 33 years of Sumatra squalls affecting Singapore and investigate the potential impact of the main modes of climate variability and atmospheric equatorial tropical waves. Highlighted results are that, on average, Sumatra squalls originate from Sumatra and the Strait of Malacca, make landfall over Singapore primarily in the morning and last about 2 h, and are more frequent from April to November. These squalls tend to be more frequent under La Niña conditions, which are associated with locally warm sea surface temperature anomalies and favourable atmospheric anomalies over the Maritime Continent region. On intraseasonal scale, the MJO may play a role in setting the westerlies and enhancing convective conditions favorable for the squalls to intensify and propagate eastward. Convectively-coupled Kelvin waves are important for the initiation and eastward propagation of the squalls over Sumatra and the Strait of Malacca, while equatorial Rossby, and mixed Rossby gravity waves influence their meridional propagation toward Singapore.

A review of post-wildfire adaptations of surface-water-quality models: Synthesis, gaps, and opportunities - Zachary M. Shephard; Trevor F. Partridge; Sheila F. Murphy; Michelle A. Walvoord; Brian A. Ebel (Science of The Total Environment, 2025)

Potential of blended byproduct caps for management of bauxite residues: How do texture and weathering impact geochemistry? - Golam Taki; Pauline F. Grierson; Helen E.A. Brand; Daniel V. Murphy; Talitha C. Santini (Resources, Conservation and Recycling, 2025)

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

Beyond phycocyanin: Environmental life cycle assessment of a European pilot scale Spirulina biorefinery - L. Braud; K. McDonnell; F. Murphy (Bioresource Technology Reports, 2025)

Closed laceration of the trachea, esophagus and guttural pouches in a mare caused by blunt trauma - M.A.F. Lopes; E. Hollenbach; E.C. Schliewert; M.A. Murphy; F. Corrêa (Journal of Equine Veterinary Science, 2024)

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Cheddar cheese production, structure and in-vitro semi-dynamic gastric digestion: The role of β-casein phenotype - Davor Daniloski; Richard M. Page; Prabin Lamichhane; Conor J. Fitzpatrick; Todor Vasiljevic; André Brodkorb; Mark Timlin; John Paul Murphy; Tom F. O'Callaghan; Noel A. McCarthy (Food Research International, 2024)

Evaluating evaporites as potential archives of lake and seawater lithium isotopic ratios: An experimental study using various natural saline fluids - Yin Li; Yang-Yang Wang; Jack G. Murphy; Mebrahtu F. Weldeghebriel; Yilin Xiao (Chemical Geology, 2024)

Spatial Intracranial Pressure Fields Driven by Blast Overpressure in Rats - Carly Norris; Susan F. Murphy; Caiti-Erin Talty; Pamela J. VandeVord (Annals of Biomedical Engineering, 2024)
Free-field blast exposure imparts a complex, dynamic response within brain tissue that can trigger a cascade of lasting neurological deficits. Full body mechanical and physiological factors are known to influence the body’s adaptation to this seemingly instantaneous insult, making it difficult to accurately pinpoint the brain injury mechanisms. This study examined the intracranial pressure (ICP) profile characteristics in a rat model as a function of blast overpressure magnitude and brain location. Metrics such as peak rate of change of pressure, peak pressure, rise time, and ICP frequency response were found to vary spatially throughout the brain, independent of blast magnitude, emphasizing unique spatial pressure fields as a primary biomechanical component to blast injury. This work discusses the ICP characteristics and considerations for finite element models, in vitro models, and translational in vivo models to improve understanding of biomechanics during primary blast exposure.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Farm electricity system simulator (FESS): A platform for simulating electricity utilisation on dairy farms - F. Buckley; J. Upton; R. Prendergast; L. Shalloo; M.D. Murphy (Computers and Electronics in Agriculture, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Parsing the toxicity paradox: Composition and duration of exposure alter predicted oil spill effects by orders of magnitude - Deborah P. French-McCay; Hilary J. Robinson; Julie E. Adams; Matthew A. Frediani; Matthew J. Murphy; Cheryl Morse; Melissa Gloekler; Thomas F. Parkerton (Marine Pollution Bulletin, 2024)

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

Tracking long-term shifts in non-native freshwater macroinvertebrates across three European countries - Mathieu Toutain; Ismael Soto; Jes Jessen Rasmussen; Zoltán Csabai; Gábor Várbíró; John F. Murphy; Paride Balzani; Antonín Kouba; David Renault; Phillip J. Haubrock (Science of The Total Environment, 2024)

Environmental and behavioural drivers of Antarctic krill distribution at the South Orkney Islands: A regional perspective - Emma F. Young; Sally E. Thorpe; Angelika H.H. Renner; Eugene J. Murphy (Journal of Marine Systems, 2024)

Relative quantitative proteomic profiling of bovine colostrum and transition milk at onset of lactation - Hannah K. Masterson; Tom F. O'Callaghan; Michael O'Donovan; John Paul Murphy; Katie Sugrue; Rebecca A. Owens; Rita M. Hickey (International Dairy Journal, 2024)

A Decade in Review: Trends in Female Authorship in Peer-Reviewed Toxicology Journals - Jennifer S. Love; George T. Loo; Lauren Murphy; Courtney Temple; Meghan B. Spyres; Alex F. Manini; Ayrn D. O’Connor (Journal of Medical Toxicology, 2024)

Freshwater invertebrate responses to fine sediment stress: A multi‐continent perspective - Morwenna McKenzie; Andrew Brooks; Marcos Callisto; Adrian L. Collins; Jessica M. Durkota; Russell G. Death; J. Iwan Jones; Marden S. Linares; Christoph D. Matthaei; Wendy A. Monk; John F. Murphy; Annika Wagenhoff; et al. (Global Change Biology, 2024)
Excessive fine sediment (particles

An epigenome-wide association study of child appetitive traits and DNA methylation - Holly A. Harris; Chloe Friedman; Anne P. Starling; Dana Dabelea; Susan L. Johnson; Bernard F. Fuemmeler; Dereje Jima; Susan K. Murphy; Cathrine Hoyo; Pauline W. Jansen; Janine F. Felix; Rosa H. Mulder (Appetite, 2023)

CEC05-05: Using Integrated Approaches to Testing and Assessment to streamline Grouping and Read-Across of solid nanomaterials - V. Stone; A. Oomen; H. Johnston; D. Hristozov; O. Schmidt; T. Stoeger; S. Aparicio; U. Vogel; W. Wohlleben; F. Murphy (Toxicology Letters, 2023)

Refining the in vitro release test method for a dapivirine-releasing vaginal ring to match in vivo performance - Diarmaid J. Murphy; Deanna Lim; Ryan Armstrong; Clare F. McCoy; Yahya H. Dallal Bashi; Peter Boyd; Tiffany Derrick; Patrick Spence; Bríd Devlin; R. Karl Malcolm (Drug Delivery and Translational Research, 2023)
Previously reported in vitro release test methods for drug-releasing vaginal rings containing poorly water-soluble drugs have described use of water-alcohol systems or surfactant solutions in efforts to maintain sink conditions. Here, as part of efforts to more closely match in vitro and in vivo release for the 25 mg dapivirine matrix-type silicone elastomer vaginal ring for HIV prevention, we have investigated alternatives to the 1:1 v/v water/isopropanol medium described previously. Specifically, we evaluated dapivirine release from rings into (i) monophasic water/isopropanol mixtures of varying compositions and (ii) biphasic buffer/octanol systems using pH 4.2 and pH 7.0 buffers. The rate and mechanism of dapivirine release were dependent upon the isopropanol concentration in the release medium, in accordance with the observed trend in drug solubility. At 0 and 10% v/v isopropanol concentrations, dapivirine release followed a partition-controlled mechansim. For media containing ≥ 20% v/v isopropanol, in vitro release of dapivirine was significantly increased and obeyed permeation-controlled kinetics. Cumulative release of ~3.5 mg dapivirine over 28 days was obtained using a water isopropanol mixture containing 20% v/v isopropanol, similar to the ~4 mg dapivirine released in vivo. Dapivirine release into the biphasic buffer/octanol system (intended to mimic the fluid/tissue environment in vivo) was constrained by the limited solubility of dapivirine in the buffer component in which the ring resided, such that cumulative dapivirine release was consistently lower than that observed with the 20% v/v isopropanol in water medium. Release into the biphasic system was also pH dependent, in line with dapivirine’s pK a and with potential implications for in vivo release and absorption in women with elevated vaginal pH. Graphical abstract

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Prevailing impacts of river management on microplastic transport in contrasting US streams: Rethinking global microplastic flux estimations - Anna Kukkola; Robert L. Runkel; Uwe Schneidewind; Sheila F. Murphy; Liam Kelleher; Gregory H. Sambrook Smith; Holly Astrid Nel; Iseult Lynch; Stefan Krause (Water Research, 2023)

Blending bauxite residues with multiple byproducts improves capping materials for tailings storage facilities - Golam Taki; Pauline F. Grierson; Grace Scullett-Dean; Helen E.A. Brand; Daniel V. Murphy; Talitha C. Santini (Journal of Environmental Management, 2023)

Pyrodiversity trade-offs: A simulation study of the effects of fire size and dispersal ability on native mammal populations in northern Australian savannas - Hugh F. Davies; Casey Visintin; Brett P. Murphy; Euan G. Ritchie; Sam C. Banks; Ian D. Davies; David M.J.S. Bowman (Biological Conservation, 2023)

Long-term trends in crayfish invasions across European rivers - Ismael Soto; Danish A. Ahmed; Ayah Beidas; Francisco J. Oficialdegui; Elena Tricarico; David G. Angeler; Giuseppe Amatulli; Elizabeta Briski; Thibault Datry; Alain Dohet; Sami Domisch; Judy England; et al. (Science of The Total Environment, 2023)

Patterns of dreissenid mussel invasions in western US lakes within an integrated gravity model framework - Carra C. Carrillo; Bianca R. Charbonneau; Safra Altman; Jacque A. Keele; Sherri F. Pucherelli; Yale J. Passamaneck; Aaron C. Murphy; Todd M. Swannack (Journal of Environmental Management, 2023)

Nitrogen isotopes indicate vehicle emissions and biomass burning dominate ambient ammonia across Colorado's Front Range urban corridor - J. David Felix; Alexander Berner; Gregory A. Wetherbee; Sheila F. Murphy; Ruth C. Heindel (Environmental Pollution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 2: global performance and future changes - Kuniko Yamazaki; David M. H. Sexton; John W. Rostron; Carol F. McSweeney; James M. Murphy; Glen R. Harris (Climate Dynamics, 2021)

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 1: selecting the parameter combinations - David M. H. Sexton; Carol F. McSweeney; John W. Rostron; Kuniko Yamazaki; Ben B. B. Booth; James M. Murphy; Leighton Regayre; Jill S. Johnson; Ambarish V. Karmalkar (Climate Dynamics, 2021)

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Influence of functional food components on gut health - Murphy L. Y. Wan; K. H. Ling; Hani El-Nezami; M. F. Wang (Critical Reviews in Food Science and Nutrition, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Effect of copper on multiple successional stages of a marine fouling assemblage - David J. McElroy; Dieter F. Hochuli; Martina A. Doblin; Richard J. Murphy; Robert J. Blackburn; Ross A. Coleman (Biofouling, 2017)

Perceptuo-motor planning during functional reaching after stroke - Margit Alt Murphy; Melanie C. Baniña; Mindy F. Levin (Experimental Brain Research, 2017)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Defective splicing of the RB1 transcript is the dominant cause of retinoblastomas - Kamil J. Cygan; Rachel Soemedi; Christy L. Rhine; Abraham Profeta; Eileen L. Murphy; Michael F. Murray; William G. Fairbrother (Human Genetics, 2017)

Gene expression profiles predictive of cold-induced sweetening in potato - Jonathan Neilson; M. Lagüe; S. Thomson; F. Aurousseau; A. M. Murphy; B. Bizimungu; V. Deveaux; Y. Bègue; J. M. E. Jacobs; H. H. Tai (Functional & Integrative Genomics, 2017)

Impairment in Mismatch Negativity but not Repetition Suppression in Schizophrenia - Brian A. Coffman; Sarah M. Haigh; Tim K. Murphy; Dean F. Salisbury (Brain Topography, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

High-Speed Laser Image Analysis of Plume Angles for Pressurised Metered Dose Inhalers: The Effect of Nozzle Geometry - Yang Chen; Paul M. Young; Seamus Murphy; David F. Fletcher; Edward Long; David Lewis; Tanya Church; Daniela Traini (AAPS PharmSciTech, 2017)

Banking on the future: progress, challenges and opportunities for the genetic conservation of forest trees - Kevin M. Potter; Robert M. Jetton; Andrew Bower; Douglass F. Jacobs; Gary Man; Valerie D. Hipkins; Murphy Westwood (New Forests, 2017)

Body size and symbiotic status influence gonad development in Aiptasia pallida anemones - Judith F. Carlisle; Grant K. Murphy; Alison M. Roark (Symbiosis, 2017)

The Jebel Ohier deposit—a newly discovered porphyry copper–gold system in the Neoproterozoic Arabian–Nubian Shield, Red Sea Hills, NE Sudan - F. P. Bierlein; S. McKeag; N. Reynolds; C. J. Bargmann; W. Bullen; F. C. Murphy; H. Al-Athbah; C. Brauhart; W. Potma; S. Meffre; S. McKnight (Mineralium Deposita, 2016)

Biochar increases availability and uptake of phosphorus to wheat under leaching conditions - Obed F. Madiba; Zakaria M. Solaiman; Jennifer K. Carson; Daniel V. Murphy (Biology and Fertility of Soils, 2016)

Monitoring and Controlling the Beet Leafhopper Circulifer tenellus in the Columbia Basin - Silvia I. Rondon; Alexzandra F. Murphy (American Journal of Potato Research, 2016)

Evaluation of Cartilage Repair by Mesenchymal Stem Cells Seeded on a PEOT/PBT Scaffold in an Osteochondral Defect - V. Barron; K. Merghani; G. Shaw; C. M. Coleman; J. S. Hayes; S. Ansboro; A. Manian; G. O’Malley; E. Connolly; A. Nandakumar; C. A. van Blitterswijk; P. Habibovic; et al. (Annals of Biomedical Engineering, 2015)

Criteria for assessing maturity of skulls in the common dolphin, Delphinus sp., from New Zealand waters - Friederike F. J. Jordan; Sinéad Murphy; Emmanuelle Martinez; Christophe Amiot; Anton van Helden; Karen A. Stockin (Marine Mammal Science, 2015)
Knowledge about the maturity status of specimens included in evolutionary, taxonomic or life history investigations is fundamentally important. This study investigated the use of the degree of cranial suture fusion, the developmental status of cranial bones, and the degree of tooth wear as indicators for cranial maturity status in Delphinus sp. from New Zealand waters. In total, 15 sutures, one joint and three nonmetric characters were assessed on 66 skulls obtained from stranded and bycaught individuals sampled between 1932 and 2011. A suture index ( SI ) was computed based on 10 sutures, in which degree of fusion was correlated with age and the three misclassification indices ( MI ), calculated for a given suture, were Delphinus sp. skulls should be regarded as cranially mature if at least two of the following criteria are met: (1) individuals assessed as sexually mature, (2) aged ≥ 11 yr, (3) SI ≥ 8, and (4) premaxilla‐maxilla fusion ≥ 75% of the length of the dorsal side of the rostrum. Presence of any number of rostral teeth worn to the gum line provided further evidence for cranial maturity.

Improving estimates of tropical peatland area, carbon storage, and greenhouse gas fluxes - I. T. Lawson; T. J. Kelly; P. Aplin; A. Boom; G. Dargie; F. C. H. Draper; P. N. Z. B. P. Hassan; J. Hoyos-Santillan; J. Kaduk; D. Large; W. Murphy; S. E. Page; et al. (Wetlands Ecology and Management, 2015)

Impacts of variations in the strength and structure of El Niño events on Pacific rainfall in CMIP5 models - Bradley F. Murphy; Hua Ye; François Delage (Climate Dynamics, 2015)

Differential disease symptoms and full-length genome sequence analysis for three strains of Tobacco etch virus - Nubia Velasquez; Mohammad J. Hossain; John F. Murphy (Virus Genes, 2015)

Developmental alterations in anxiety and cognitive behavior in serotonin transporter mutant mice - Yasufumi Sakakibara; Yoshiyuki Kasahara; F. Scott Hall; Klaus-Peter Lesch; Dennis L. Murphy; George R. Uhl; Ichiro Sora (Psychopharmacology, 2014)

Assessing Potato Psyllid Haplotypes in Potato Crops in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Joseph E. Munyaneza; Alexzandra F. Murphy; Silvia I. Rondon; Brandon Thompson; Alexander V. Karasev; Erik J. Wenninger; Nora Olsen; James M. Crosslin (American Journal of Potato Research, 2014)

Assessment of the CMIP5 global climate model simulations of the western tropical Pacific climate system and comparison to CMIP3 - Michael R. Grose; Jaclyn N. Brown; Sugata Narsey; Josephine R. Brown; Bradley F. Murphy; Clothilde Langlais; Alex Sen Gupta; Aurel F. Moise; Damien B. Irving (International Journal of Climatology, 2014)
A set of 27 global climate models from the Coupled Model Inter‐comparison Project Phase 5 ( CMIP5 ) ensemble are assessed for their performance for the purpose of making future climate projection studies in the western tropical Pacific and differences to Coupled Model Inter‐comparison Project Phase 3 ( CMIP3 ) are assessed. The CMIP5 models show some improvements upon CMIP3 in the simulation of the climate in the western tropical Pacific in the late 20th century. There are fewer CMIP5 models with very poor skill scores than in CMIP3 for some measures and a small group of the well‐performing models in CMIP5 have lower biases than in an equivalent group from CMIP3 . These best‐performing models could be particularly informative for studying certain climate sensitivities and feedbacks in the region. There is evidence to reject one model as unsuitable for making regional climate projections in the region, and another two models unsuitable for analysis of the South Pacific Convergence Zone (SPCZ). However, while there have been improvements, many of the systematic model biases in the mean climate in CMIP3 are also present in the CMIP5 models. They are primarily related to the shape of the transition between the Indo‐Pacific warm pool and equatorial cold tongue, and the associated biases in the position and orientation of the SPCZ and Inter‐Tropical Convergence Zone, as well as in the spatial pattern, variability and teleconnections of the West Pacific monsoon, and the simulation of El Niño Southern Oscillation. Overall, the results show that careful interpretation and consideration of biases is required when using CMIP5 outputs for generating regional climate projections for the western tropical Pacific, particularly at the country scale, just as there was with CMIP3 .

There is a critical weight range for A ustralia's declining tropical mammals - Brett P. Murphy; Hugh F. Davies (Global Ecology and Biogeography, 2014)
Many mammals in A ustralia's tropical north are in severe decline, yet understanding of the drivers of this decline is remarkably limited. Recently, F isher et al . ( Global Ecology and Biogeography , 2014, 23 , 181−190) examined the traits that are associated with declining marsupial species in northern A ustralia. They concluded that, in this region, declines are most pronounced in the smallest species (those with the lowest body mass). This is in strong contrast to the significant declines that occurred earlier in central and southern A ustralia before the mid 20th century, which were most pronounced in medium‐sized species, the so‐called ‘critical weight range’ (35−5500 g). Here we show that F isher et al . have misinterpreted their dataset; in northern A ustralia, the pattern of mammal decline in relation to body mass is remarkably similar to that in central and southern A ustralia, with mammal decline strongly concentrated in the critical weight range, suggesting fundamentally similar drivers between north and south.

Highly depleted isotopic compositions evident in Iapetus and Rheic Ocean basalts: implications for crustal generation and preservation - J. Brendan Murphy; John W. F. Waldron; David I. Schofield; Tiffany L. Barry; Adrian R. Band (International Journal of Earth Sciences, 2014)

Cancer risk and genotype–phenotype correlations in PTEN hamartoma tumor syndrome - Marry H. Nieuwenhuis; C. Marleen Kets; Maureen Murphy-Ryan; Helger G. Yntema; D. Gareth Evans; Chrystelle Colas; Pal Møller; Frederik J. Hes; Shirley V. Hodgson; Maran J. W. Olderode-Berends; Stefan Aretz; Karl Heinimann; et al. (Familial Cancer, 2014)

Evaluation of Beet Leafhopper Transmitted Virescence Agent Damage in the Columbia Basin - Alexzandra F. Murphy; Silvia I. Rondon; Ruben Marchosky; Jeremy Buchman; Joseph Munyaneza (American Journal of Potato Research, 2014)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Haplotypes of the Potato Psyllid, Bactericera cockerelli, on the Wild Host Plant, Solanum dulcamara, in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Erik Echegaray; Alexzandra F. Murphy; Silvia I. Rondon; Joseph E. Munyaneza; James M. Crosslin (American Journal of Potato Research, 2013)

An evaluation of the serotonin system and perseverative, compulsive, stereotypical, and hyperactive behaviors in dopamine transporter (DAT) knockout mice - Meredith A. Fox; Micaella G. Panessiti; F. Scott Hall; George R. Uhl; Dennis L. Murphy (Psychopharmacology, 2013)

First Report of Potato Psyllids, Bactericera cockerelli, Overwintering in the Pacific Northwest - Alexzandra F. Murphy; Silvia I. Rondon; Andrews S. Jensen (American Journal of Potato Research, 2013)

Predator hunting mode influences patterns of prey use from grazing and epigeic food webs - Gina M. Wimp; Shannon M. Murphy; Danny Lewis; Margaret R. Douglas; Ramya Ambikapathi; Lie’Ann Van-Tull; Claudio Gratton; Robert F. Denno (Oecologia, 2013)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Trapped in desert springs: phylogeography of Australian desert spring snails - Nicholas P. Murphy; Martin F. Breed; Michelle T. Guzik; Steven J. B. Cooper; Andrew D. Austin (Journal of Biogeography, 2012)
Aim We investigate the phylogeographical history and determine the time‐scale of population divergence of hydrobiid freshwater snails (genus Trochidrobia ) inhabiting groundwater springs in the Australian desert. We test the hypothesis that divergence between geographically distinct snail populations occurred simultaneously due to their isolation in hydrologically discrete spring systems, i.e. ‘trapped in desert springs’. Location Groundwater springs of the Great Artesian Basin (GAB) in central Australia. Methods DNA sequence data from the mitochondrial cytochrome c oxidase subunit I gene and the nuclear 28S and internal transcribed spacer rRNA genes were used to reconstruct phylogenetic relationships within and among three species of Trochidrobia (Hydrobiidae): T. punicea (13 spring groups, n = 90) , T. smithi (12 spring groups, n = 62) and T. minuta (2 spring groups, n = 4). Bayesian relaxed molecular clock analyses and approximate Bayesian computation were used to date lineage divergence and distinguish between alternative biogeographical scenarios. Results The diversification of the three Trochidrobia species probably occurred between 2.54 and 9.3 Ma, prior to the formation of the springs c . 1 Ma. Intraspecific divergences within the two widespread species occurred after the formation and colonization of the springs. Coalescent modelling and molecular clock analyses supported a simultaneous radiation of five allopatric intraspecific snail lineages within T. punicea (two lineages) and T. smithi (three lineages) across the GAB springs examined. Main conclusions The analyses support the ‘trapped in desert springs’ hypothesis for the diversification of intraspecific lineages within the species T. punicea and T. smithi . This hypothesis suggests that the formation of deserts around Lake Eyre in the early Pleistocene led to the hydrological isolation of spring complexes in the GAB, resulting in significant molecular divergence, but no morphological divergence, of Trochidrobia snail populations.

Advancing the use of minirhizotrons in wetlands - C. M. Iversen; M. T. Murphy; M. F. Allen; J. Childs; D. M. Eissenstat; E. A. Lilleskov; T. M. Sarjala; V. L. Sloan; P. F. Sullivan (Plant and Soil, 2012)

Preface: Multiscale analysis of the Mt Isa–McArthur region, Northern Australia - F. C. Murphy (Australian Journal of Earth Sciences, 2011)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Distinguishing habitat types and the relative influences of environmental factors on patch occupancy for a butterfly metapopulation - Monte P. Sanford; Dennis D. Murphy; Peter F. Brussard (Journal of Insect Conservation, 2011)

A review of the evolution of viviparity in squamate reptiles: the past, present and future role of molecular biology and genomics - Bridget F. Murphy; Michael B. Thompson (Journal of Comparative Physiology B, 2011)

Increased primary production shifts the structure and composition of a terrestrial arthropod community - Gina M. Wimp; Shannon M. Murphy; Deborah L. Finke; Andrea F. Huberty; Robert F. Denno (Ecology, 2010)
Numerous studies have examined relationships between primary production and biodiversity at higher trophic levels. However, altered production in plant communities is often tightly linked with concomitant shifts in diversity and composition, and most studies have not disentangled the direct effects of production on consumers. Furthermore, when studies do examine the effects of plant production on animals in terrestrial systems, they are primarily confined to a subset of taxonomic or functional groups instead of investigating the responses of the entire community. Using natural monocultures of the salt marsh cordgrass Spartina alterniflora , we were able to examine the impacts of increased plant production, independent of changes in plant composition and/or diversity, on the trophic structure, composition, and diversity of the entire arthropod community. If arthropod species richness increased with greater plant production, we predicted that it would be driven by: (1) an increase in the number of rare species, and/or (2) an increase in arthropod abundance. Our results largely supported our predictions: species richness of herbivores, detritivores, predators, and parasitoids increased monotonically with increasing levels of plant production, and the diversity of rare species also increased with plant production. However, rare species that accounted for this difference were predators, parasitoids, and detritivores, not herbivores. Herbivore species richness could be simply explained by the relationship between abundance and diversity. Using nonmetric multidimensional scaling (NMDS) and analysis of similarity (ANOSIM), we also found significant changes in arthropod species composition with increasing levels of production. Our findings have important implications in the intertidal salt marsh, where human activities have increased nitrogen runoff into the marsh, and demonstrate that such nitrogen inputs cascade to affect community structure, diversity, and abundance in higher trophic levels.

Landscape genetics: where are we now? - ANDREW STORFER; MELANIE A. MURPHY; STEPHEN F. SPEAR; ROLF HOLDEREGGER; LISETTE P. WAITS (Molecular Ecology, 2010)
Landscape genetics has seen rapid growth in number of publications since the term was coined in 2003. An extensive literature search from 1998 to 2008 using keywords associated with landscape genetics yielded 655 articles encompassing a vast array of study organisms, study designs and methodology. These publications were screened to identify 174 studies that explicitly incorporated at least one landscape variable with genetic data. We systematically reviewed this set of papers to assess taxonomic and temporal trends in: (i) geographic regions studied; (ii) types of questions addressed; (iii) molecular markers used; (iv) statistical analyses used; and (v) types and nature of spatial data used. Overall, studies have occurred in geographic regions proximal to developed countries and more commonly in terrestrial vs. aquatic habitats. Questions most often focused on effects of barriers and/or landscape variables on gene flow. The most commonly used molecular markers were microsatellites and amplified fragment length polymorphism (AFLPs), with AFLPs used more frequently in plants than animals. Analysis methods were dominated by Mantel and assignment tests. We also assessed differences among journals to evaluate the uniformity of reporting and publication standards. Few studies presented an explicit study design or explicit descriptions of spatial extent. While some landscape variables such as topographic relief affected most species studied, effects were not universal, and some species appeared unaffected by the landscape. Effects of habitat fragmentation were mixed, with some species altering movement paths and others unaffected. Taken together, although some generalities emerged regarding effects of specific landscape variables, results varied, thereby reinforcing the need for species‐specific work. We conclude by: highlighting gaps in knowledge and methodology, providing guidelines to authors and reviewers of landscape genetics studies, and suggesting promising future directions of inquiry.

Isolation of microsatellites via enrichment and a sequence tagged method in a South American lizard with suspected parental care, Liolaemus leopardinus - Andrew R. Murphy; Michael G. Gardner; Stanley F. Fox (Conservation Genetics Resources, 2009)

Bioengineering and Imaging Research Opportunities Workshop V: A Summary - William R. Hendee; Kevin Cleary; Richard L. Ehman; Gary D. Fullerton; Warren S. Grundfest; John Haller; Christine Kelley; Anne E. Meyer; Robert F. Murphy; William Phillips; Vladimir P. Torchilin (Annals of Biomedical Engineering, 2008)

Magnetotelluric soundings and crustal architecture at Century mine, northern Australia - F. C. Murphy; J. Cull; T. J. Lee; S. K. Lee; Y. Song (Australian Journal of Earth Sciences, 2008)

A review of recent climate variability and climate change in southeastern Australia - Bradley F. Murphy; Bertrand Timbal (International Journal of Climatology, 2008)
Southeastern Australia (SEA) has suffered from 10 years of low rainfall from 1997 to 2006. A protracted dry spell of this severity has been recorded once before during the 20th century, but current drought conditions are exacerbated by increasing temperatures. Impacts of this dry decade are wide‐ranging, so a major research effort is being directed to better understand the region's recent climate, its variability and climate change. This review summarizes the conditions of these 10 years and the main mechanisms that affect the climate. Most of the rainfall decline (61%) has occurred in autumn (March–May). Daily maximum temperatures are rising, as are minimum temperatures, except for cooler nights in autumn in the southwest of SEA closely related to lower rainfall. A similar rainfall decline occurred in the southwest of western Australia around 1970 that has many common features with the SEA decline. SEA rainfall is produced by mid‐latitude storms and fronts, interactions with the tropics through continental‐scale cloudbands and cut‐off lows. El Niño‐Southern Oscillation impacts on SEA rainfall, as does the Indian Ocean, but neither has a direct influence in autumn. Trends have been found in both hemispheric (the southern annular mode) and local (sub‐tropical ridge) circulation features that may have played a role in reducing the number and impact of mid‐latitude systems around SEA, and thus reducing rainfall. The role of many of these mechanisms needs to be clarified, but there is likely to be an influence of enhanced greenhouse gas concentrations on SEA climate, at least on temperature. Copyright © 2007 Royal Meteorological Society

Evaluation of genetic variation of attack and resistance in lodgepole pine in the early stages of a mountain pine beetle outbreak - Alvin D. Yanchuk; John C. Murphy; Kimberly F. Wallin (Tree Genetics & Genomes, 2008)

Microbial response to the addition of glucose in low-fertility soils - F. C. Hoyle; D. V. Murphy; P. C. Brookes (Biology and Fertility of Soils, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Larval development of the Ambon damselfish Pomacentrus amboinensis , with a summary of pomacentrid development - B. F. Murphy; J. M. Leis; K. D. Kavanagh (Journal of Fish Biology, 2007)
Morphological development of the larvae of the Ambon damselfish Pomacentrus amboinensis from the Great Barrier Reef, Australia, is described from 34 reared specimens (2·5–13·0 mm standard length), and two wild settlement‐stage larvae (10·8–11·3 mm) captured in light traps. Reared larvae emerged from demersal eggs at c . 2·5 mm, underwent notochord flexion at 4·0–4·5 mm, and settled at 11–13 mm at 19–21 days after hatching (within the known range for wild larvae). Reared larvae grew at 0·3 mm day −1 (preflexion) to 0·5 mm day −1 (postflexion). Development was direct with few specializations for pelagic existence and was typical of pomacentrids. Head spination consisted of very weak spines on the preopercle, opercle, interopercle, subopercle and supracleithrum. Development of the olfactory system and retina are also described. A summary of published descriptions of early life‐history stages of pomacentrid damselfishes is provided ( n = 15% of known species). Larvae of several genera ( e.g. Abudefduf , Chromis and Stegastes ) are deeper‐bodied and more ‘hunchbacked’ than P. amboinensis . Larvae of other genera ( e.g. Amblyglyphidodon, Chrysiptera and Neoglyphidodon ) are similar to P. amboinensis . Larvae of only three other Pomacentrus species have been described, and they are similar to P. amboinensis in body morphology, pigmentation and head spination.

Synthesis and Structure-Activity Relationship of [Nle10]Neurokinin A (4–10) Analogs with Constraint in the Backbone and at Position Six - Ferenc Ötvös; Dmitry S. Gembitsky; Richard F. Murphy; Sándor Lovas (International Journal of Peptide Research and Therapeutics, 2007)

Large-Scale Automated Analysis of Location Patterns in Randomly Tagged 3T3 Cells - Elvira García Osuna; Juchang Hua; Nicholas W. Bateman; Ting Zhao; Peter B. Berget; Robert F. Murphy (Annals of Biomedical Engineering, 2007)

Decoding IgE Fc receptors - Ming Zhang; Richard F. Murphy; Devendra K. Agrawal (Immunologic Research, 2007)

Fish and blue crab assemblage structure in a U.S. mid Atlantic coastal lagoon complex - Robert F. Murphy; David H. Secor (Estuaries and Coasts, 2006)

Different Signal Responses to Lamprey GnRH-III in Human Cancer Cells - Krisztina Herédi-Szabó; Richard F. Murphy; Sándor Lovas (International Journal of Peptide Research and Therapeutics, 2006)

A comparison of the European Water Framework Directive physical typology and RIVPACS-type models as alternative methods of establishing reference conditions for benthic macroinvertebrates - John Davy-Bowker; Ralph T. Clarke; Richard K. Johnson; Jiri Kokes; John F. Murphy; Svetlana Zahrádková (Hydrobiologia, 2006)

Distribution of orogenic gold deposits in relation to fault zones and gravity gradients: targeting tools applied to the Eastern Goldfields, Yilgarn Craton, Western Australia - Frank P. Bierlein; Finbarr C. Murphy; Roberto F. Weinberg; Terry Lees (Mineralium Deposita, 2006)

Sustainable engineering: a model for engineering education in the twenty-first century? - David T. Allen; Cynthia F. Murphy; Braden Allenby; Cliff Davidson (Clean Technologies and Environmental Policy, 2006)

Transferrin recycling and dextran transport to lysosomes is differentially affected by bafilomycin, nocodazole, and low temperature - Gnther Baravalle; Daniela Schober; Marlis Huber; Nora Bayer; Robert F. Murphy; Renate Fuchs (Cell and Tissue Research, 2005)

Isolation and characterization of the bovine Stearoyl-CoAdesaturase promoter and analysis of polymorphisms in the promoter region in dairy cows - Aileen F. Keating; Catherine Stanton; John J. Murphy; Terry J. Smith; R. Paul Ross; Michael T. Cairns (Mammalian Genome, 2005)

Environmental Consequences of Intensively Managed Forest Plantations in the Pacific Northwest - John P. Hayes; Stephen H. Schoenholtz; Mitschka J. Hartley; Glen Murphy; Robert F. Powers; Dean Berg; Steven R. Radosevich (Journal of Forestry, 2005)
Environmental consequences of intensively managed forest plantations (IMFP) are manifested primarily through influences on biodiversity, soils, and water resources. These consequences may be positive, neutral, or negative, depending on the spatial and temporal context and site-specificdetails. Many aspects of environmental consequences of IMFPs are increasingly understood, but significant gaps in our knowledge remain. Societal environmental goals and objectives of IMFPs remain poorly articulated and fuel a lively, often heated, social dialogue that will likely continuefor some time to come.

Spatial structure in lotic macroinvertebrate communities in England and Wales: relationship with physical, chemical and anthropogenic stress variables - John F. Murphy; John Davy-Bowker (Hydrobiologia, 2005)

Variation in the response of Mimulus guttatus (Scrophulariaceae) to herbivore and virus attack - Micky D. Eubanks; David E. Carr; John F. Murphy (Evolutionary Ecology, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Twinning and the Incidence of Breast and Gynecological Cancers (United States) - Rachel E. Neale; David M. Purdie; Michael F. G. Murphy; Geraldine P. Mineau; Timothy Bishop; David C. Whiteman (Cancer Causes & Control, 2004)

Variability of southeastern Queensland rainfall and climate indices - Bradley F. Murphy; Joachim Ribbe (International Journal of Climatology, 2004)
The variability of climate indices and rainfall in southeastern (SE) Queensland (Qld) is studied. Using high‐resolution gridded rainfall data for all of Australia and global sea‐surface temperatures (SSTs), the relationship between Australia‐wide rainfall (and in SE Qld in particular) and SST indices and the southern oscillation index (SOI) have been investigated. It is found that SE Qld is more subject to the breakdown of correlations between the SOI and rainfall than any other part of Australia. Model predictions suggest that this is probable in the future. Considering only time scales longer than interannual, it was found that SSTs in the central tropical Pacific Ocean (TPO; represented by the Niño‐4 index) correlated best with SE Qld rainfall. Eastern TPO (Niño‐3) SSTs and the SOI produced successively weaker correlations. The time series of the second modes of variability of SSTs over the Pacific and Indian Oceans were shown to have limited impact on SE Qld rainfall variability. The data were split into periods before and after 1946, when Australian mean rainfall changed. Whereas the SOI correlations with rainfall in SE Australia were similar in both periods, in SE Qld the correlations were very weak in the earlier period (0.06) but very strong in the later period (0.72). The Niño‐4 index correlated better than the Niño‐3 index in both periods, but both indexes showed smaller changes from the earlier to the later periods than the SOI. Copyright © 2004 Royal Meteorological Society.

Coronary Stent Strut Size Dependent Stress–Strain Response Investigated Using Micromechanical Finite Element Models - P. Savage; B. P. O' Donnell; P. E. McHugh; B. P. Murphy; D. F. Quinn (Annals of Biomedical Engineering, 2004)

The Stress–Strain Behavior of Coronary Stent Struts is Size Dependent - B. P. Murphy; P. Savage; P. E. McHugh; D. F. Quinn (Annals of Biomedical Engineering, 2003)

The susceptibility and response of inbred and outbred Mimulus guttatus to infection by Cucumber mosaic virus - David E. Carr; John F. Murphy; Micky D. Eubanks (Evolutionary Ecology, 2003)

The complete nucleotide sequence of Pepper mottle virus -Florida RNA - C. E. Warren; J. F. Murphy (Archives of Virology, 2003)

Using Remote Sensing to Assess Russian Forest Fire Carbon Emissions - A. S. Isaev; G. N. Korovin; S. A. Bartalev; D. V. Ershov; A. Janetos; E. S. Kasischke; H. H. Shugart; N. H. F. French; B. E. Orlick; T. L. Murphy (Climatic Change, 2002)

The relationship between Pepper mottle virus source leaf and spread of infection through the stem of Capsicum sp. - J. F. Murphy (Archives of Virology, 2002)

The effects of tryptophan depletion on cognitive and affective processing in healthy volunteers - F. Murphy; K. Smith; P. Cowen; T. Robbins; B. Sahakian (Psychopharmacology, 2002)

Development of Multiplexed Fluorescence Microbead Covalent Assays (FMCAs) for Pesticide Biomonitoring - R. E. Biagini; D. M. Murphy; D. L. Sammons; J. P. Smith; C. A. F. Striley; B. A. MacKenzie (Bulletin of Environmental Contamination and Toxicology, 2002)

Genus Coltivirus (family Reoviridae): genomic and morphologic characterization of Old World and New World viruses - H. Attoui; F. Mohd Jaafar; P. Biagini; J.-F. Cantaloube; P. de Micco; F. A. Murphy; X. de Lamballerie (Archives of Virology, 2002)

Location and Structure of the Human FHR-5 Gene - Jennifer L. McRae; Brendan F. Murphy; Helen J. Eyre; Grant R. Sutherland; Joanna Crawford; Peter J. Cowan (Genetica, 2002)

Prediction of uphill time-trial bicycling performance in humans with a scaling-derived protocol - D. P. Heil; O. F. Murphy; A. R. Mattingly; B. K. Higginson (European Journal of Applied Physiology, 2001)

Application of Rhizobacteria for Induced Resistance - Geoffrey W. Zehnder; John F. Murphy; Edward J. Sikora; Joseph W. Kloepper (European Journal of Plant Pathology, 2001)

Induction of resistance in tomato against cucumber mosaic cucumovirus by plant growth-promoting rhizobacteria - Geoffrey W. Zehnder; Changbin Yao; John F. Murphy; Edward R. Sikora; Joseph W. Kloepper (BioControl, 2000)

Nanoscale topography of the basement membrane underlying the corneal epithelium of the rhesus macaque - G. A. Abrams; S. L. Goodman; P. F. Nealey; M. Franco; C. J. Murphy (Cell and Tissue Research, 2000)

Aquatic macrophyte distribution in relation to water and sediment conditions in the Itaipu Reservoir, Brazil - L. Mauricio Bini; Sidinei M. Thomaz; Kevin J. Murphy; Antonio F. M. Camargo (Hydrobiologia, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Analysis of isolates recovered from multiple sites of the nasopharynx of children colonized by nontypeableHaemophilus influenzae - J. M. Bernstein; D. Dryja; N. Yuskiw; T. F. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Analysis of sites of foot and mouth disease virus persistence in carrier cattle via the polymerase chain reaction - M. L. Prato Murphy; R. F. Meyer; C. Mebus; A. A. Schudel; M. Rodriguez (Archives of Virology, 1994)

Modifications to the rules for virus nomenclature - M. A. Mayo; F. A. Murphy (Archives of Virology, 1994)

Somerset: A new chipping potato variety - R. H. True; A. F. Reeves; R. V. Akeley; H. J. Murphy; G. A. Porter; R. H. Cole; J. Watts; B. J. Christ; F. E. Manzer (American Journal of Potato Research, 1990)

Electron microscopic and antigenic studies of uncharacterized viruses. II. Evidence suggesting the placement of viruses in the familyBunyaviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopy and antigenic studies of uncharacterized viruses. I. Evidence suggesting the placement of viruses in familiesArenaviridae, Paramyxoviridae, orPoxviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopic and antigenic studies of uncharacterized viruses. III. Evidence suggesting the placement of viruses in the familyReoviridae - H. G. Zeller; N. Karabatsos; C. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Campbell 14: A verticillium resistant round white potato variety - A. F. Reeves; C. E. Cunningham; R. L. Nickeson; R. V. Akeley; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1985)

Sunrise: An early maturing, golden nematode resistant, round, white potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1985)

Yankee Supreme: A new bruise-resistant potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; R. L. Nickeson; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1984)

Islander: A golden nematode resistant potato variety for fresh market and chipping - A. F. Reeves; R. V. Akeley; F. E. Manzer; H. J. Murphy; R. H. True; J. B. Sieczka; D. D. Moyer (American Journal of Potato Research, 1984)

Yankee Chipper: A new golden nematode resistant potato variety with wide adaptation in the northeastern United States - A. F. Reeves; R. V. Akeley; F. E. Manzer; H. J. Murphy; R. H. True; J. B. Sieczka; D. D. Moyer (American Journal of Potato Research, 1984)

Allagash Russet: A new potato variety from maine - A. F. Reeves; R. V. Akeley; F. E. Manzer; H. J. Murphy; R. H. True (American Journal of Potato Research, 1980)

Delta Gold: A new potato variety with yellow flesh, high solids and high quality for baking and processing - A. F. Reeves; R. E. Webb; D. C. Merriam; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1980)

Temperature-sensitive mutants of influenza A virus. Transfer of the twots-1 A 2ts lesions present in the Udorn/72-ts-1 A 2 donor virus to the influenza A/Alaska/6/77 (H 3 N 2) wild type virus - B. R. Murphy; F. T. Wood; J. G. Massicot; R. M. Chanock (Archives of Virology, 1980)

Temperature-sensitive mutants of influenza A virus: Evaluation of the Alaska/77-ts-1 A 2 temperature-sensitive recombinant virus in seronegative adult volunteers - B. R. Murphy; R. M. Chanock; R. G. Douglas; R. F. Betts; D. H. Waterman; H. P. Holley; D. L. Hoover; S. Suwanagool; D. R. Nalin; M. M. Levine (Archives of Virology, 1980)

Viruses isolated from reptiles: Identification of three new members of the familyRhabdoviridae - T. P. Monath; C. B. Cropp; Christina L. Frazier; F. A. Murphy; Sylvia G. Whitfield (Archives of Virology, 1979)

Lyssavirus infection of muscle spindles and motor end plates in striated muscle of hamsters - Alyne K. Harrison; F. A. Murphy (Archives of Virology, 1978)

Rabies pathogenesis - F. A. Murphy (Archives of Virology, 1977)

Cold adapted variants of influenza A - S. B. Spring; H. F. Maassab; A. P. Kendal; B. R. Murphy; R. M. Chanock (Archives of Virology, 1977)

Characterization of Orungo virus, an orbivirus from Uganda and Nigeria - O. Tomori; A. Fabiyi; F. Murphy (Archives of Virology, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

The flavor of small immature tubers compared with mature Katahdin tubers - Elizabeth F. Murphy; Ruth H. True; J. M. Hogan; H. J. Murphy (American Journal of Potato Research, 1974)

Effects of differential rates of nitrogen and phosphorus on early blight in potatoes - G. M. Barclay; H. J. Murphy; F. E. Manzer; F. E. Hutchinson (American Journal of Potato Research, 1973)

The determination of a mid-scale reference standard for baked potato mealiness - Elizabeth F. Murphy; Ruth H. True; John M. Hogan (American Journal of Potato Research, 1969)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Effect of tetrachloronitrobenzene (Fusarex) on emergence and yield of potatoes. Part II. — Northeast - H. J. Murphy; M. J. Goven; J. C. Campbell; C. F. Everett; J. D. Harrington; R. L. Sawyer (American Journal of Potato Research, 1968)

Detection threshold of sensory panels for mealiiness of baked potatoes as related to specific gravity differences - Elizabeth F. Murphy; Ruth H. True; John M. Hogan (American Journal of Potato Research, 1967)

Intranuclear formation of filaments in herpesvirus hominis infection of mice - F. A. Murphy; Alyne K. Harrison; Sylvia G. Whitfield (Archives of Virology, 1967)

Effect of physiological maturity and storage temperature on emergence and yield of potatoes - H. J. Murphy; F. E. Manzer; M. J. Goven; D. C. Merriam (American Journal of Potato Research, 1967)

Potato flavor quality as affected by two fungicides - Elizabeth F. Murphy; Franklin E. Manzer (American Journal of Potato Research, 1965)

Effect of pentachloronitrobenzene soil treatment on flavor of potatoes - Jennie L. Brogdon; Elsie H. Dawson; A. P. Benson; Elizabeth F. Murphy (American Journal of Potato Research, 1965)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

The specific gravity, mealiness, and flavor of baked Maine potatoes as related to fungicide treatment - Elizabeth F. Murphy; Reiner Bonde; Franklin E. Manzer (American Journal of Potato Research, 1963)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

Observations on genetic, physiological, and environmental factors affecting the vitamin C content of Maine-grown potatoes - Elizabeth F. Murphy; W. Franklin Dove; Robert V. Akeley (American Journal of Potato Research, 1945)